Literature review: The effect of health promotion on adolescents knowledge, attidue, and behavior about balanced nutrition during the Covid-19 pandemic - Dewi Nufrianto, Bulan Suci; Ayu Handani, Melinda Dwi (Jurnal Kesehatan Langkat Berseri (JURKESLASER), 2021)
Adolescents are categorized as vulnerable to nutritional problems so that they are at risk for health. The prevalence of nutritional status of school-age children and adolescents based on Riskesdas 2013 data, BMI/U (thin and very thin) is 10.56%. The 2018 National Basic Health Research Survey (in Unicef Indonesia, 2021) shows that the burden of malnutrition in Indonesia is quite large, with more than a quarter of the youth population aged 13-15 years experiencing stunting or around 26%, 9% underweight (thin), and 16% obesity. Among adolescents aged 16-18 years, 27% were stunted, 8% were underweight, and 14% were obese. This study uses a literature review method and aims to determine the knowledge, attitudes, and behavior of adolescents on a balanced nutritional. The results of a systematic study obtained a number of articles that matched the keywords and there were 15 articles analyzed. The population of balanced nutrition food research data from 2017-2021 is based on 15 articles analyzed with research samples of adolescents. Several health promotion influences have been identified, among others are knowledge, attitude, behavior, age and gender.